2018
DOI: 10.1111/ped.13563
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia‐modified albumin in preterm infants born to mothers with pre‐eclampsia

Abstract: Serum IMA in addition to the prevalence of SGA were significantly increased in the PE group. Cord blood IMA, therefore, might be a predictive biomarker for SGA in PE pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
1
6
1
Order By: Relevance
“…As serum IMA levels are indicative of ischemia, IMA levels should be increased in IUGR infants. However conflicting results are reported about the concentration of cord blood IMA in IUGR infants (17)(18)(19). In this study, we found that cord blood IMA levels were significantly higher in SGA infants than AGA infants.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…As serum IMA levels are indicative of ischemia, IMA levels should be increased in IUGR infants. However conflicting results are reported about the concentration of cord blood IMA in IUGR infants (17)(18)(19). In this study, we found that cord blood IMA levels were significantly higher in SGA infants than AGA infants.…”
Section: Discussioncontrasting
confidence: 51%
“…Furthermore, elevated maternal serum IMA levels have been recently demonstrated in early normal pregnancy, supporting the hypothesis that pregnancy is always associated with immense stress in order to accommodate the increasing demands of the developing fetus (16). Then, OS has been reported to be notable in the development of PE and IMA has been reported as a novel predictive biomarkker for PE to reflect the OS in the pathogenesis (8) and some studies have demonstrated the correlation of serum IMA with severity of preeclampsia (7,17). In our study increased cord blood IMA levels of infants of preeclamptic mothers are indicative of higher OS status.…”
Section: Discussionmentioning
confidence: 90%
“…It was demonstrated that the drop in albumin in plasma and the rise in IMA occurred in ischemia pregnancies as a result of inflammation and endothelial cell activity being activated. Similarly, Özdemir et al found that cord blood IMA was significantly higher and albumin was markedly lower (18) . Van Rijn et al explained this by impaired placental circulation, which is related to restricted fetal growth (19) .…”
Section: Discussionmentioning
confidence: 86%
“…Also, some clinical studies have recently indicated elevated levels of IMA in neonatal sepsis, preterm infants born to mothers with preeclampsia, preterm infants with respiratory distress syndrome, infants of diabetic mother, and ischemic conditions such as necrotizing enterocolitis in newborns. [7][8][9] This study aimed to assess the value of IMA as a diagnostic marker for neonatal hypoxic-ischemic encephalopathy (HIE).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies about IMA levels and hypoxia have been published ( Table 1 ). Also, some clinical studies have recently indicated elevated levels of IMA in neonatal sepsis, preterm infants born to mothers with preeclampsia, preterm infants with respiratory distress syndrome, infants of diabetic mother, and ischemic conditions such as necrotizing enterocolitis in newborns [ 7 - 9 ].…”
Section: Introductionmentioning
confidence: 99%